تذکرۂ اختلافِ روایات :بذل المجہود کا مطالعہ و جائزہ: Textual Variations in Hadith: A Study of Badhl al- Majhud fi Hall Sunan Abi Dawud - Haroon, Muhammad; Manj, Muhammad Shahbaz (FIKR-O NAZAR فکر ونظر, 2020)
It is not rare to find a tradition (riw┐yah) in compilations of ╒┐dith with varying words. Many commentators have dealt with this issue in their commentaries of ╒┐dith. Mawl┐n┐ Khal┘l A╒mad Sah┐ranp┴ri (1852-1927) was a prominent Indian scholar, who is especially renowned for his work of ╒┐dith. He has written a commentary on Sunan of Ab┴ D┐w┴d titled Badhl al- Majh┴d f┘ ╓all Sunan Ab┘ D┐w┴d , which spans over fourteen volumes. He has also dealt with issue of textual variations ╒┐dith at numerous places in his commentary. The present study attempts to examine Sah┐ranp┴ri’s treatment of the problem in Badhl al- Majh┴d.